2001
DOI: 10.1097/00004728-200107000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Crohn Disease of the Small Bowel: Spiral CT Evaluation After Oral Hyperhydration with Isotonic Solution

Abstract: Our method allowed adequate distension of the small bowel for spiral CT studies, thus resulting in a safe and effective alternative to small-bowel spiral CT enema, which can be used in patients that refuse the nasojejunal balloon catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 12 publications
3
51
0
7
Order By: Relevance
“…In accordance with other authors [6], we decided to use a solution of PEG as an oral hypodense contrast medium. The choice of PEG is based on the fact that it is a well-known solution in widespread use for the preparation of endoscopic studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In accordance with other authors [6], we decided to use a solution of PEG as an oral hypodense contrast medium. The choice of PEG is based on the fact that it is a well-known solution in widespread use for the preparation of endoscopic studies.…”
Section: Discussionmentioning
confidence: 89%
“…We are aware that there is no agreement in the literature about the usefulness of performing intestinal preparation before CT examination. Many authors [1,6,11] advise a light diet free of fruit and vegetables for 2 days before CT and the L M Minordi, A Vecchioli, P Mirk and L Bonomo administration of laxatives the day before. A few authors [12,13] advise fasting for 8-12 h prior to CT. We have been recommending our intestinal preparation for radiological study since 1980 and since 2000 for CT examination, and have found that the intestinal loops are usually clean so we plan to continue recommending this preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, Mazzeo et al [50] reported that in over 20% of patients CT enterography was inadequate owing to poor distension. However, a smaller study performed by Wold et al [8] showed no significant difference in distension between CT enteroclysis and enterography.…”
Section: Comparing Ct Enterography With Other Modalitiesmentioning
confidence: 99%
“…Whereas both MRI [7] and MDCT enteroclysis [8] allow optimal lumen distension, oral administration of contrast agent with the proper choice of oral contrast material and adequate timing can produce good results [9,10], is more patient-friendly and less time consuming. For MDCT, the choice of oral contrast agent is usually determined by the anatomical SI region of interest and the clinical question to be answered ( Figure 1).…”
Section: Mdctmentioning
confidence: 99%